On the finding of brachiopod in metamorphic garnet-bearing rocks on the Middle Urals - K. S. Ivanov (Izvestiâ Uralʹskogo Gosudarstvennogo Gornogo Universiteta, 2017)
The authors provide paleontological and mineralogical description of the finding of the brachiopod of Atrypinae gen. et sp. indet. of the Silurian (Llandovery) – Late Devonian (Frasnian) age in a well-formed garnet-almandine crystal. Field geologist D. L. Suslov was the one who found the brachiopod in high-aluminous gneisses in Verkholovsky garnet mine, which is a part of the Evgenie-Maximilianovsky (Palkinsky) mineral mines located in the southeastern part of the Verkhisetsky granite batholite, on the territory of the historical-landscape park "Istoki Iseti". The Verkholovsky garnet mine is located on the southern slope of Pup Mountain, about 6 km west of Ekaterinburg city, on the eastern slope of the Middle Urals. The stock of the Ural Geological Museum stores the sample containing the brachiopod imprint, its measures are 3 × 2.2 × 1.6 cm and it looks like a parallel aggregate of several garnet-almandine crystals. Main habitus forms of the garnet individuals are rhombododecahedron d{110} and tetragontrioctahedron n{211}, the latter forming thin facets of the rhombododecahedron edges. The shell imprint is not in the garnet crystals, but in the base of the sample, among the fine-grained light-brown mass, whose thickness is not more than 2–3 mm. The fine-grained mass previously probably was a carbonate matrix of the brachiopod, and during the growth of the garnet at the border of two heterogeneous media (carbonate and silicate), a local metasomatic process of substituting the garnet aggregate for the primary (carbonate) substance manifested. The article also contains a brief geological sketch of the place of the finding and an overview of information about other similar findings. Chemical U-Th-Pb-dating allowed to determine the age of monazite inclusions in garnet (344 million years).